EFFECT OF CASSAVA TUBER PROCESSING ON Candida albicans GROWTH ON MANIHOT DEXTROSE AGAR - Patilaya, Popi; Sumantri, Imam Bagus; Keliat, Jane Melita (Talenta Publisher, 2025)
This study evaluated the effect of cassava tuber processing on Candida albicans growth on Manihot Dextrose Agar (MDA). The sliced cassava tubers were divided into three groups. G1 was milled and dried in an oven at 60°C. G2 was directly dried in the oven. G3 was milled without drying. Each group was soaked in distilled water (1,000 mL) for 15 min and filtered with a flannel cloth. The filtrate was oven-dried, then pulverized to obtain the cassava powder. The powder (8 g) was combined with dextrose (20 g) and agar (15 g). The mixture was suspended in distilled water (1,000 mL), boiled, and sterilized at 121°C for 15 min. The solution was placed into a petri dish and allowed to form agar media. The media derived from G1, G2, and G3 were considered as F1, F2, and F3. A suspension of C. albicans was cultured on the media and incubated for 48 h. The fungal growth was observed by calculating the viable colonies. The data were analyzed with one-way ANOVA and followed by Duncan’s test at the confidence level of 95%. The results showed that C. albicans grown on media F1, F2, and F3 had colony numbers of 128±2.08 x 105 cfu/mL, 64±5.57 x 105 cfu/mL, and 44±3.51 x 105 cfu/mL, respectively. Statistical analysis indicated a significant difference in the fungal growth on the three media (p < 0.05). This study proved that the processing methods of cassava tubers for MDA significantly affected the growth of C. albicans.